Full Contractual Capacity: Use of Age for Conferment of Capacity - LOO, Wee Ling (Institutional Knowledge at Singapore Management University, 2010)
The Singapore Civil Law (Amendment) Act, effective 1 March 2009, lowered the age of full contractual capacity from 21 to 18 with the sole aim of encouraging entrepreneurship among the young. This article examines if currently available scientific evidence and practical considerations indicate: (i) whether there is utility in using an age-based criterion for conferring full contractual capacity and thus denying legal protection in contracting in light of the need to balance protection of minors against encouraging youthful entrepreneurship; (ii) even if useful, whether full contractual capacity should be conferred from age 18 in the Singapore context; and (iii) if extra measures ought to have accompanied the lowering of the age of full contractual capacity to mitigate potential problems affecting consumer-minors and entrepreneur-minors who are now deprived of previously available legal protection under contract law.